Konstruksi Pendidikan Relasi Kiai Dan Santri Di Pondok Pesantren Lintang Songo Piyungan Yogyakarta - Ahmad Shofiyuddin Ichsan (IAI Darussalam, 2019)
This study aims to reveal leadership in Islamic Boarding School (Pondok Pesantren) Lintang Songo Piyungan Bantul Yogyakarta and the construction of educational relations between Kiai and santri in the context of a multidisciplinary approach. The results of the study show that there are three approaches produced. In the Normative approach, there are five things that can be revealed. 1). Straightening intentions, 2). Choosing a teacher and glorifying science and experts, 3). Learning and deliberation diligently, 4). Studying overseas and endure the difficulties which they experience, and 5). Working and praying for sufficiency. Whereas in the Psychology approach, it appears that the relationship between Kiai and santri has a very good attachment. Kiai Heri never takes the position himself as a leader and santri as subordinates, but their relationship is very intimate, like parents to their children. Furthermore, in the Sociology approach, Pondok pesantren Lintang Songo could be studied in three environments, namely material, social, and symbolic environments.